Media Papan Catur untuk Meningkatkan Maharah Qira’ah - Khoirun Nisa'; Zakiyatul Abidah; Titin Fidiatin Nur A (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
The learning process of maharah qira'ah for class VII students is still lacking in terms of pronunciation, fluency, and understanding of the meaning of reading. Many students feel bored and lack enthusiasm in learning Arabic, especially maharah qira'ah. For this reason, researchers use media that can foster enthusiasm and understanding in learning maharah qira'ah, namely by using a chess board media. This study used a quantitative experimental approach with the One Group Design method. Data collection techniques in this study were interviews, observation, documentation, tests and questionnaires. The results of this study are that the chessboard learning media is suitable for implementation in learning Arabic, especially maharah qira'ah, the research was carried out for three meetings, the steps for applying the chessboard media were: the researcher divided the groups. provide a story translation. Each chess has a mufrodat. Then the groups are asked to discuss until they are arranged into stories. After being composed, one group read aloud, this is evidenced by the results of the pre-test totaling 1460, with an average score of 66.37 and a post-test score of 1720, with an average of 81.46. So it is proven that there is an increase in the value of 260. This is evidenced by the t test value being higher than the t table value at a significant level of 0.05 and 0.01% in the T distribution test, namely 12.368> 2.07 and 12.368> 2.83.